Socioeconomic indicators and prevalence of anemia - children under 3 years, Sapallanga Health Center, 2017 - García Inga , Belinda Olga (2020)
Objectives: The situation of anemia in the Sapallanga Health Center is high and reaches a rate of The prevalence of 57% of the total number of children in this district is worrisome and was the reason for this research, having formulated us as the main problem: What socioeconomic indicators are related to the prevalence of anemia in children under 3 years of age served in the health center of Sapallanga in 2017? Material and Methods: Was basic, correlated and cross-sectional level. The population and at the same time shows; of the present study comprised a total of 70 children under 3 years of age with anemia in the Sapallanga Health Center according to the nominal standard. Conclusions: At the end of the investigation, it was found that there are socioeconomic indicators that are significantly related to the prevalence of anemia in children under 3 years of age attended in the health center of Sapallanga in 2017 and are: Public network drain service (p value = 0.028 <0.05); electricity service (p value = 0.000 <0.05); father’s work (p value = 0.016 <0.05) and number of members per room (p value = 0.000 <0.05).